Tilting Body Vehicles on Slovak Railways – Potential for Use and Parameters to Be Considered - Miloslav Klinko; Juraj Grencik (Communications - Scientific letters of the University of Zilina, 2008)
Competition between various transport modes has been a characteristic feature of the last decades not only in the world yet in Slovakia. Passenger rail transport proves to be most suitable for medium distances with high traffic intensity. In Slovakia this is valid first of all for Bratislava – Zilina – Kosice line. One solution for increasing travel speed and ride comfort is using the tilting body trains. In the paper theoretical considerations for use of tilting body vehicles are presented. On the example of Zilina – Kosice railway line we show a potential for remarkable reduction of travel time which is the most expected benefit of the new train technology. But we present also parameters which should be considered when thinking about use of new technology.